Contribution of Creative Economy and Tourism to Inclusive Economic Development in Indonesia - Fadilla, Meita Indah; Hariyanti, Dini; Putri, Farah Nabilla (Universitas Pasundan, 2024)
The role of the creative economy and tourism as one of the economic catalysts encourages the realization of inclusive development in Indonesia. This study aims to analyze the existence of a creative economy and tourism workforce, the wages/salaries of the creative economy and tourism workforce and domestic tourists, and the inclusive economic development. This research method uses quantitative statistical analysis with the Least Squares Dummy Variable (LSDV) technique. The research has sample of 34 provinces in Indonesia in 2018-2021. The results indicate that the rate of the creative economy and tourism labor, and the rate of tourism labor wages/salaries affect inclusive economic development positively and significantly. Meanwhile, the rate of domestic tourists and the wage/salary rate of creative economy labor affect inclusive economic development positively and insignificantly. This research implies that government and community involvement is needed to create a sustainable creative economy and tourism through various efforts, such as ecotourism, technology development, and policy realization, to increase innovation and creativity in this sector.